Validation of 2004 ISMP medication safety self assessment tool for use in Philippine Military Hospital - Lim, Ma. Dolores M. (Thesis -- (Masters in Arts in Nursing). -- University of the Philippines Manila.)
Background of the study: Medication error is considered as one of the major problem of the healthcare system. Several programs have been adopted to promote medication safety such as computerization, use of bar coding, pharmacist participation etc. In the United States of America they use the 2004 ISMP Medication Safety Self Assessment for Hospitals to help assess the medical practices of hospitals and identify opportunities for improvement. However, in the Philippines medication safety self-assessment is not a regular part of the programs of the hospital. Likewise, there is no existing tool that would assess medication safety in hospitals in the Philippines. There is a potential for using this tool in local hospitals here but its validity, applicability and feasibility still need to be tested.
Objectives of the Study: The main purpose of this study is to determine whether the 2004 ISMP Medication Safety Self Assessment Tool is a valid and appropriate tool to use in Philippine Military Hospitals. 1. To establish the content validity of 2004 ISMP Medication Safety Self Assessment Tool as it pertains to the Philippine scenario. 1.1 To determine which items in the 2004 ISMP Tool are relevant in measuring medication safety practices of hospitals in the Philippines; 1.2 To determine if there are other items that important and relevant in measuring medication safety practices of hospitals that are not currently contained in the 2004 ISMP Tool. 2. To identify the supports and potential barriers within hospitals systems, including acceptability of potential end-users and administrators, in adopting the ISMP Tool in terms of the following: 2.1 Structure; 2.2 Policies and procedures; 2.3 Human resources; 2.4 Other resources.
Methodology:This is a methodological research to determine whether the 2004 ISMP Medication Safety Self Assessment Tool for Hospitals can be used in Philippine military hospitals. To determine content validity this study utilized content validity index rating and interview of five medical experts who are representatives from hospital licensing and accreditation agencies and associations of hospital and nursing administration such as the Department of Health Philippine Health Insurance. To determine the applicability and feasibility of the tool, opinion of experts and possible end users that include hospital administrators, medical officers, nurses and pharmacist from five major hospitals of the Armed Forces of the Philippines were utilized.
Summary of Findings: All the experts agree that the 2004 ISMP tool is a valid tool in evaluation medication practices in the light of Philippine setting. All the items under all 20 core characteristics were highly significant with average weighted means ranging from 4.72 ? 5.0. They likewise agree that the tool can be applied in hospitals in the Philippines. However, they said that implementing the tool may be difficult. Hospitals may not readily accept the tool because it may entail additional cost and they may find the tool too sophisticated for them. They also identified the following issues in addition to budgetary constraints that may affect its implementation: a) computerization, b) role of clinical pharmacist, c) role of drug and therapeutic board and d) culture on medication error. They likewise suggested revising some of the items in the tool to make it more appropriate and acceptable for hospitals in the Philippines. Their suggested revisions were grouped into the following: a) Change word that are not commonly used in the Philippines b) merge related items.
The possible end users on the other hand varied in their responses when asked about the applicability of the tool. Majority of them failed to recognize the actual purpose of the tool which is to bring medication safety awareness among hospitals and improve the safety of medication use. They have assessed each item in the tool solely on the basis of their applicability in Philippine hospitals and are not evaluated as to the possibility of their implementation at all. They find the tool too sophisticated for hospitals in the Philippines but when asked to accomplish the tool, results show that the participating hospitals scored lowest in core characteristics 3 and 4 with AWM of 55.7% and 58.8% respectively and scored highest in core characteristics 10 and 16 with 91.6% and 84.88% AWM respectively. Comparing the experts? validity index rating and the AWM of core characteristics tested among participating hospitals, core characteristics 3 and 2 scored lowest in both.
Conclusion and Recommendations: The 2004 ISMP tool is a valid tool in evaluating the medication practices in the light of Philippine setting. There may be some issues that may affect its applicability and acceptability but nonetheless, it is good tool that may help hospitals in the Philippines improve its medication practices. Experts suggested some revisions to make it more appropriate and acceptable for Philippine used. With this, it is highly recommended that proper coordination with the ISMP for revision be made. It is also recommended to test the tool in other hospitals to further evaluate its usefulness.
Keywords: Philippine Military Hospitals; ISMP; Self-Assessment.